Evaluation of water use efficiency in irrigated agriculture supported by satellite images - Enrique Palacios-Vélez; José L. Espinosa-Espinosa; Luis A. Palacios-Sánchez (Tecnología y ciencias del agua, 2018)
Palacios-Vélez, E., Palacios-Sánchez, L. A., & Espinosa- Espinosa, J. L. January-February, 2018). Evaluation of water use efficiency in irrigated agriculture supported by satellite images. Water Technology and Sciences (in Spanish), 9(1), 31- 38, DOI: 10.24850/j-tyca-2018-01-02.